2016
DOI: 10.1038/tp.2016.208
|View full text |Cite
|
Sign up to set email alerts
|

Defining the role of corticotropin releasing factor binding protein in alcohol consumption

Abstract: The corticotropin releasing factor (CRF) exerts its effects by acting on its receptors and on the binding protein (CRFBP), and has been implicated in alcohol use disorder (AUD). Therefore, identification of the exact contribution of each protein that mediates CRF effects is necessary to design effective therapeutic strategies for AUD. A series of in vitro/in vivo experiments across different species were performed to define the biological discrete role of CRFBP in AUD. First, to establish the CRFBP role in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 47 publications
(66 reference statements)
1
51
0
Order By: Relevance
“…Indeed, the CRF-BP has recently received attention as a potential target for its role in alcohol use disorder (Haass-Koffler et al 2016, Ketchesin et al 2016); and, particularly, its role in the escalation of alcohol drinking may involve interaction with CRF 2 receptors (Albrechet-Souza et al 2015, Quadros et al 2016). Receptor activity modifying proteins (RAMPs) are other molecules that interact directly with the CRF system, as RAMP2 binds CRF 1 and increases its surface expression and signaling sensitivity (Wootten et al 2013).…”
Section: Targeting and Validating Drug Action In Humansmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the CRF-BP has recently received attention as a potential target for its role in alcohol use disorder (Haass-Koffler et al 2016, Ketchesin et al 2016); and, particularly, its role in the escalation of alcohol drinking may involve interaction with CRF 2 receptors (Albrechet-Souza et al 2015, Quadros et al 2016). Receptor activity modifying proteins (RAMPs) are other molecules that interact directly with the CRF system, as RAMP2 binds CRF 1 and increases its surface expression and signaling sensitivity (Wootten et al 2013).…”
Section: Targeting and Validating Drug Action In Humansmentioning
confidence: 99%
“…SNPs in the CRHBP (10kD) fragment, rs10055255, rs10062367 , and rs7728378 were each shown to be associated with increased risk of alcohol drinking and/or anxiety in patients with alcohol use disorder (Haass-Koffler et al 2016). …”
Section: Recent Genetic and Molecular Findings In Humansmentioning
confidence: 99%
“…Wang, You, Rice, & Wise, 2007). The CRF-BP has recently received attention as a potential target for its role in alcohol use disorder (Haass-Koffler et al, 2016; Ketchesin, Stinnett, & Seasholtz, 2016), and its role in the escalation of alcohol drinking may involve its interaction with CRF 2 (Albrechet-Souza et al, 2015; Quadros, Macedo, Domingues, & Favoretto, 2016). Intriguingly, recent gene variant studies in humans have shown that the CRHBP rs1875999 locus was associated with risk for both cocaine and heroin addiction in African Americans in a study of heroin addicts ( n = 314), cocaine addicts ( n = 281), and healthy controls ( n = 208) (Levran, Peles, et al, 2014; Levran, Randesi, et al, 2014).…”
Section: Role For Crf-crf1 Systems In Animal Models Of Addictionmentioning
confidence: 99%
“…Intriguingly, recent gene variant studies in humans have shown that the CRHBP rs1875999 locus was associated with risk for both cocaine and heroin addiction in African Americans in a study of heroin addicts ( n = 314), cocaine addicts ( n = 281), and healthy controls ( n = 208) (Levran, Peles, et al, 2014; Levran, Randesi, et al, 2014). SNPs in the CRHBP (10kD) fragment, rs10055255, rs10062367 , and rs7728378 were each associated with increased risk of alcohol drinking and/or anxiety in patients with alcohol use disorder (Haass-Koffler et al, 2016). …”
Section: Role For Crf-crf1 Systems In Animal Models Of Addictionmentioning
confidence: 99%
“…Indeed, compared to rodents, where there is limited CRFR2 expression in the CeA (Van Pett et al 2000), primates express high density of CRFR2 in the CeA (Sanchez et al 1999), although the functional relevance of this has not yet been determined. CRFBP in rodents was recently shown to interact with CRFR2 in the VTA to influence binge-like alcohol drinking (Haass-Koffler et al 2016). Therefore, a deeper understanding of the relationship between alcohol and brain CRF system plasticity and signaling, especially CRFR2 signaling and CRF-BP, may be necessary to effectively leverage the brain CRF system as a therapeutic target for reducing excessive alcohol drinking and negative affect in at least a subset of humans living with AUD.…”
Section: 5 Human Studiesmentioning
confidence: 99%